Fast computer simulation method of thrombus formation on pipe orifice flow - Nattakarn Numpanviwat (2018)
© 2016 ICIC International. This paper presents the performance of the parallel algorithm for simulating thrombus formation on pipe orifice flow by using a PETSc software library package. Since the computational cost for bio-fluid problems is very expensive, an efficient algorithm such as parallel computing is necessary in order to overcome this limitation. The parallel program reduces the computational time by dividing workload to calculate simultaneously for each processor or computer. This will help researchers and physicians for medical diagnosis and development of medical devices. The blood flow used in this analysis is modeled by the incompressible Navier-Stokes equations with a partially patched modified k − ϵ model. Moreover, the platelet adhesion model is used for predicting the formation of thrombus. We perform the numerical experiments on the orifice configuration. The results show that our program can reduce the computation time by increasing the number of processors.